Effect of gamma irradiation on the dielectric properties of the TlGaS2 single crystal - Mustafaeva, S. N.; Asadov, M. M.; Ismaіlov, A. A. (Видавництво Львівської політехніки, 2012)
The real (ε') and imaginary (ε'') parts of complex dielectric permittivity and ac-conductivity (sаc) across the layers of TlGaS2 single crystal have been measured in the frequency range f = 5 × 104 – 3.5 × 107 Hz before and after gamma irradiation with doses Dg from 5 ´ 104 to 2.15 ´ 106 rad. It was shown that the accumulation of radiation dose in TlGaS2 single crystal leads to tangible increase in ε'' and to increase of ε'' dispersion. The main parameters of localized states in TlGaS2 single crystal before and after gamma irradiation were evaluated from high- frequency dielectric measurements.
Keywords: single crystal; frequency dispersion; gamma irradiation; localized states; hopping conductivity; dielectric permittivity